Thyre, Harald, and Ravnunge-Tue - Sawyer, Birgit (Hikuin, 2005)
For centuries the two Jelling stones (DR 41 and 42) have been the subject of lively discussion. Various problems have been debated, but, as far as I know, nobody has hitherto asked why two Danish kings in succession were so careful to commemorate Thyre, the wife of Gorm and the mother of Harald. Not only is Thyre commemorated on these two stones; in Gorm’s inscription she is also referred to as tanmarkaR but. During the 1930s and 1940s it was vigorously debated whether this epithet referred to Thyre or Gorm. It is now generally accepted that it refers to Thyre as ‘Denmark’s ornament’.1 Quite apart from the linguistic and stylistic arguments supporting this interpretation, one wonders how the alternative interpretation ever gained ground; if the praise had not concerned Thyre, why was she commemorated at all - and on two rune-stones?